Cultural Malpractices and Associated Factors Among Mothers Attending Postnatal Care Within Six Weeks After Delivery at Gelemso General Hospital, Eastern Ethiopia - Jemaludin Sadik; Dureti Abdurahman; Adera Debella; Elias Yadeta; Rudwan Yasin Abrahim; Nano Belema; Bilisuma Girma; Magarsa Lami; Tegenu Balcha (Health Services Insights)
Background: Cultural malpractices are socially shared perspectives and traditionally accepted behaviors experienced in a certain society that harm maternal health. In Ethiopia, about 18% of infant deaths occur due to cultural malpractice. However, evidence of cultural malpractice during the postnatal period is not well understood in Ethiopia, particularly in West Hararghe. Moreover, there is no study conducted on cultural practice during the postnatal period in this study area. Therefore, this aimed to assess the magnitude and factors associated with cultural malpractice among mothers attending postnatal care within 6 weeks after delivery at Gelemso General Hospital, Eastern Ethiopia. Methods: Institutional-based cross-sectional study design was conducted among 407 mothers attending postnatal care with their babies at Gelemso General Hospital. The study participants were selected by systematic random sampling technique. Data were collected using a pretested and structured interviewer-administered questionnaire. The collected data were entered into EpiData version 4.6 and exported to Statistical Package of Social Sciences version 27 for analysis. Descriptive statistics were computed to describe the characteristics of the participants. Bivariable and multivariable logistic regression analyses were fitted to identify factors associated with the outcome variable. Adjusted odds ratios along a 95% confidence interval were used to report the result and show the strength of the association. A P -value < .05 was used to declare a significant association. The results were presented using figures, tables, graphs, and text. Results: The study revealed that the magnitude of cultural malpractice during the postnatal period was 70.0% (95% CI: 65%, 74%). Lack of ANC visit (AOR = 3.3; 95% CI: 1.03, 10.27), partner’s being a farmer (AOR = 7.4; 95% CI: 2.11, 26.48), distance to health facility (AOR = 3.6; 95% CI: 1.68, 7.65), having greater than 5 alive children (AOR = 3.5; 95% CI: 1.25, 9.84) were factors significantly associated with cultural malpractice during the postnatal period. Conclusions: This study noted that more than two-thirds of participants committed cultural malpractice during the postnatal period. Therefore, emphasizing the importance of ANC follow-up, and encouraging home visits of postnatal mothers by professionals especially for those rural residents and remoter to health facilities may contribute to reducing the cultural malpractice.